HUBUNGAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG ANEMIA DENGAN KETERATURAN IBU HAMIL DALAM MENGKONSUMSI TABLET FE DI WILAYAH KERJA PUSKESMAS SUNGAI LIMAU KABUPATEN PADANG PARIAMAN - Ningsih, Mahdalena Prihatin; Rahmawati, Lisa (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
Anemia in pregnancy is a national and international problem. Anemia in pregnant women has a great influence on the quality of human resources. Anemia during the pregnancy has an impact to mother and fetus. The causes of anemia in pregnant women is because of the lack of knowledge about food that good for them besides the lack of food intake that contain Fe. The highest number of anemia in pregnant women was found in Sungai Limau Community Health Center Working Area as big as 102 from 643 pregnant women, or 16.4 %. The coverage number of Fe Tablet was also the lowest in this Community Health Center as about 58.32 %. Meanwhile, from the Hb test result it was found that 80 from 226 pregnant women experienced the anemia. Research objective: to know about The Relationship of Pregnant Mother Anemia Knowledge Level with The Regularity in Consuming Fe Tablet in Sungai Limau Padang Pariaman District Community Health Center Working Area. Research type: Analytical descriptive with cross sectional approach. Population is all 52 the pregnant women in Korong Sungai Sirah and Korong Duku Sungai Limau Community Hearth Center working area until June. Sample was taken as total sampling. The data was analyzed by using univariate and bivariate. Research result showed that there is relationship between pregnant women knowledge related to anemia and regularity in consuming Fe tablet in Sungai Limau Community Hearth Center working area Padang Pariaman district. Conclusion: most respondent had low knowledge about Fe tablet, most respondent didn’t consume Fe tablet regularly, and there was relationship between Pregnant Mother Anemia Knowledge Level with The Regularity in Consuming Fe Tablet in Sungai Limau Padang Pariaman District Community Health Center Working Area. Key words: Pregnancy, Anemia